Associations Between Achievement Goal Orientations, Preferred Learning Practices, and Motivational Evaluations of Learning Environment Among Finnish Military Reservists - Pulkka, Antti-Tuomas; Budlong, Laura (Frontiers in Psychology, 2022)
In this study it was examined whether individuals' self-efficacy, preferred forms in learning and evaluations of the learning environment vary as a function of their goal orientation profiles. It was also explored whether the preferred forms in learning played a role in this association. Participants were 177 reservists of Finnish Defence Forces participating in rehearsal training exercises. Four homogeneous groups based on goal orientation profiles were found: mastery-oriented (n=47, 26.5%), success-performance-oriented (n=49, 27.7%), indifferent (n=43, 24.3%), and avoidance-oriented (n=38, 21.5%). The mastery-oriented group and the success-performance-oriented group reported higher levels in self-efficacy, legislative form in learning, and mastery goal structure when compared to the avoidance-oriented group or to the indifferent group. The avoidance-oriented reported elevated levels of perceived strain and performance goal structure in comparison to the mastery-oriented group. Controlling the learners’ preferences for different forms in learning revealed some slight differences in the observed pattern of between-group differences regarding perceptions of performance goal structure and self-efficacy. Controlling for the legislative form of learning diminished the difference between the mastery-oriented and the avoidance-oriented in perceptions of performance goal structure and controlling for the executive form of learning revealed differences between success-performance oriented and the indifferent and the avoidance oriented. The role of the learning environment in highlighting certain types of activities in learners’ choices and the relevance of this regarding their goal preferences is discussed.